Tinjauan Yuridis Tindak Pidana Pencemaran Nama Baik Berdasarkan Putusan Mahkamah Konstitusi Nomor 105/PUU – XXII/2024 - Irwan Irawan; Amirulloh Amirulloh; Malik Ibrahim; Andri Editia Gunawan; Heriyanto Heriyanto (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Law constitutes a set of rules that must be observed and implemented by every individual. The concept of law formation is an integral part of the broader meaning of legal policy to be implemented as a guideline for the management of the state and societal life. Law is a necessity for all components of the nation and state to create security and order, thereby providing a sense of justice. General elections (Pemilu) conducted directly by the people, from the people and for the people represent a means of realizing sovereignty for the state to produce democratic governance based on Pancasila and the Constitution of 1945. The implementation of elections conducted directly, freely, generally and secretly must be carried out honestly and fairly, capable of achieving national integration, professionalism and accountability in order to establish the position of the people as the central primary entity holding primary sovereignty. This research employs a normative juridical legal research methodology utilizing a statutory approach and a conceptual approach. The findings of this research demonstrate that the legal concept concerning elections is dependent upon legal policy that functions as a determinative activity in the pattern and formation of legislation concerning elections, which is formulated to monitor and reform such law as a determination of politics related to democracy within this state. This research aims to understand the impact of the implementation of legal policy within the electoral system conducted in the post-reform era and represents an expression of legal policy within the legal enforcement system in Indonesia.